Caractérisation pragmatique des phases et déterminants de l’enrôlement des élèves en difficulté par des professeurs des écoles - Éric Saillot (Recherches en Éducation)
This text presents a descriptive and comprehensive research, based on professional didactic (Pastré, Mayen, Vergnaud, 2006, Vinatier, 2009) and analysis of the speeches-in-interaction (Kerbrat-Orecchioni, 2005), especially teachers’ speech acts (Austin, 1970; Kerbrat-Orecchioni, 2008). This type of speech acts can be observed in several school situations. However, from 2008 to 2013, French school-teachers have experienced a new professional mission called « aide personnalisée » in order to help pupils in difficulties. This research aims at analyzing teacher’s discourse in order to describe and characterize the three main steps of pupils’ enrolment and the five factors of this professional decisive process for teachers.